Dampak Penggunaan Media Sosial Facebook Bagi Ibu Rumah Tangga - Sinta Dwi Ramadhani; Tiara Indri Astuti; Andhita Risko Faristiana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Facebook is one of the most used social media platforms. Facebook offers a variety of features, including status updates, photos, videos, user-generated content, and even a user-to-user marketplace. The trend of appearing on social media is currently dominated by housewives. This study aims to This research aims to find out the social media that is often used by housewives ladder. the average duration of using social media and knowing their opinions about the use of social media. Data collection is done through literature study, interviews. The purpose of this study is: To find out what features are most often used by housewives in using Facebook social media, To find out the impact of using Facebook social media among housewives Changes in the behavior of respondents using Facebook among housewives The impact of the use of Facebook social media consists of 2 impacts, namely positive and negative impacts. Positive impacts include: As household harmony, entrepreneurial development, online business. Negative impacts include: Abandoned household affairs, fraud and disputes. Housewives